(untitled) (Journal of Humanitarian and Applied Sciences, 2025)
In a time when voices abound but true stances are scarce, poetry reorders meanings and unveils contradictions hidden behind masks. In the verses before us, the poet delivers a critical discourse marked by severe reproach—without flattery or subtle hints—directed at the elites of society who chose silence, preferring to remain mute rather than speak the truth. This text is not merely poetic expression; it is an ethical and intellectual position that exposes complicity with tyranny, condemns submission, and restores dignity to the honest word. The elite—whether intellectual, political, or cultural—derive their status from their ability to embody the conscience of society and to articulate what the masses cannot or dare not say. When they abandon this role, they become nothing more than a hollow class, falsifying reality, siding with tyranny, and pursuing privileges.